Developing maximal strength for combat sports athletes - Magnani Branco, Braulio Henrique; Franchini, Emerson (Revista de Artes Marciales Asiáticas, 2021)
This chapter deals with historical aspects of strength training, contextualizing the relevance of strength training for combat sports to maximize the performance of grapplers, strikers, and mixed martial artists. Scientific articles were listed that presented data related to maximum strength in the leading research databases. Scientific evidence presented in official and simulated matches, and official competitions are presented. Likewise, longitudinal studies on the development of maximal strength in combat sports athletes, maximal strength tests for combat sports athletes (dynamic, isometric, and isokinetic tests), and reference for maximal strength (dynamic and isometric exercises) values in several exercises, as well as normative tables are presented. Another point approached was training prescription for muscle hypertrophy and maximal strength development (dynamic and isometric) for combat sports athletes.